Promote Students' Learning Skills with Three Wisdoms: Case Study of Students in Sathing Phra District, Songkhla Province - Chaisongkram, Phra adisak Vihitoo; vachirapirat, Phramethee (Journal of Dhamma for Life, 2025)
This thesis has the following objectives: 1) To study the Threefold Wisdom (Punya 3) in Theravada Buddhism. 2) To study the learning skills of students in schools located in Sathing Phra District, Songkhla Province. 3) To promote the learning skills of students in schools located in Sathing Phra District, Songkhla Province using the Threefold Wisdom as a framework. This study employed a mixed-methods research design. The quantitative research involved high school students (upper secondary level) in Sathing Phra District, Songkhla Province, during the academic year 2025. The sample size was determined using Krejcie and Morgan’s table, resulting in 196 participants from a population of 407 students. The qualitative research involved in-depth interviews with 10 experts (monks and lay scholars). The research findings revealed that 1) Students' opinions regarding the promotion of learning skills using the Threefold Wisdom were, overall, at the highest level. When considering each aspect individually, it was found that Cintāmaya-paññā (wisdom through reflection) had the highest mean score, followed by Bhāvanāmaya-paññā (wisdom through development/practice), while Sutamaya-paññā (wisdom through hearing) had the lowest mean score. 2) The design of activities to promote learning skills in schools in Sathing Phra District was found to be consistent with Bloom’s Taxonomy. The focus was on systematically developing all six domains of cognitive skills, including enhancing memory through the use of diverse media, fostering understanding through discussions and self-summarization, applying knowledge in real-life situations via simulated activities, and developing analytical skills through open-ended questioning. Furthermore, schools encouraged the synthesis of knowledge from multiple sources through integrated project-based learning and cultivated evaluative thinking grounded in moral and ethical reasoning. Students engaged in real-world projects such as reducing plastic waste and producing bio-fermented liquids. They also participated in debate forums and Dhamma discussion activities, which enhanced their critical thinking skills and moral reasoning. This comprehensive approach helped students develop not only academic knowledge but also essential life skills, ethics, and the ability to live thoughtfully and wisely in contemporary society.